Formation of an exceptionally stable ketene during phototransformations of bicyclo[2.2.2]oct-5-en-2-ones having mixed chromophores - Ghosh, Asitanga (Beilstein Journal of Organic Chemistry, 2020)
Photochemical reactions of bicyclo[2.2.2]oct-5-en-2-ones having mixed chromophores like a 5,6 dibenzoyl moiety and bulky electron-deficient substituents like phenyl or isopropenyl at the bridgehead position were analyzed for the first time in different solvents and upon irradiation with different wavelengths. In all cases, a regioselective photoinduced 1,5-phenyl migration leading to vinyl ketenes from the more congested site of the molecule to the less congested one has been observed. The ketenes were exceptionally stable both in air and solution. Its stability studies in acetonitrile through time-dependent UV absorption spectra revealed that it remained almost unchanged at least for a couple of weeks.
Keywords: α,β- and β,γ-enones; bridgehead position; ketene; mixed chromophores

(untitled) - Zimmerman, H. E.; Armesto, D. (Chem. Rev., 1996)
and references cited therein.

(untitled) - Hixson, S. S.; Mariano, P. S.; Zimmerman, H. E. (Chem. Rev., 1973)

(untitled) - Dauben, W. G.; Lodder, G.; Ipaktschi, J. (Top. Curr. Chem., 1975)

(untitled) - Houk, K. N. (Chem. Rev., 1976)

Rearrangements of Enones in Ground and Excited States - Schuster, D. I. (Photochemical Rearrangements of Enones, 1980)

CRC Handbook of Organic Photochemistry and Photobiology - Singh, V. (CRC Press, 2003)

(untitled) - Eichenberger, H.; Tsutsumi, K.; de Weck, G.; Wolf, H. R. (Helv. Chim. Acta, 1980)

(untitled) - Pfenninger, E.; Poel, D. E.; Berse, C.; Wehrli, H.; Schaffner, K.; Jeger, O. (Helv. Chim. Acta, 1968)

(untitled) - Maiti, B. C.; Singh, R.; Lahiri, S. (J. Chem. Res., Synop., 1993)

(untitled) - Maiti, B. C.; Singh, R.; Lahiri, S. (J. Photochem. Photobiol., A, 1995)

(untitled) - Maji, D.; Singh, R.; Mostafa, G.; Ray, S.; Lahiri, S. (J. Org. Chem., 1996)

(untitled) - Maiti, B. C.; Lahiri, S. (Tetrahedron, 1998)

(untitled) - Chanda, M.; Maji, D.; Lahiri, S. (Chem. Commun., 2001)

(untitled) - Yadav, S.; Banerjee, S.; Maji, D.; Lahiri, S. (Tetrahedron, 2007)

(untitled) - Banerjee, S.; Yadav, S.; Lahiri, S. (Org. Lett., 2009)

(untitled) - Sengupta, A.; Chakraborty, I.; Ghosh, A.; Lahiri, S. (Tetrahedron, 2011)

(untitled) - Ghosh, A.; Chakraborty, I.; Adarsh, N. N.; Lahiri, S. (Tetrahedron, 2010)

(untitled) - Griffin, G. W.; O'Connell, E. J. (J. Am. Chem. Soc., 1962)

(untitled) - Zimmerman, H. E.; Dürr, H. G. C.; Lewis, R. G.; Bram, S. (J. Am. Chem. Soc., 1962)

(untitled) - Murty, B. A. R. C.; Kumar, C. V.; Dabral, V.; Das, P. K.; George, M. V. (J. Org. Chem., 1984)

(untitled) - Singh, R.; Sinha, A.; Lahiri, S. (J. Chem. Res., Synop., 1992)

(untitled) - Padwa, A.; Crumrine, D.; Shubber, A. (J. Am. Chem. Soc., 1966)